Immunogenicity and safety of lyophilized and liquid dengue tetravalent vaccine candidate formulations in healthy adults: a randomized, phase 2 clinical trial. Issue 10 (2nd October 2020) - Turner, Mark; Papadimitriou, Athanasia; Winkle, Peter; Segall, Nathan; Levin, Michael; Doust, Matthew; Johnson, Casey; Lucksinger, Gregg; Fierro, Carlos; Pickrell, Paul; Raanan, Marsha; Tricou, Vianney; et al.
ABSTRACT: Takeda has developed a live-attenuated dengue tetravalent vaccine candidate (TAK-003) which has been shown to be immunogenic with acceptable reactogenicity in phase 1 trials. In agreement with World Health Organization prequalification requirements for dengue vaccines, Takeda has manufactured a lyophilized formulation of TAK-003 that allows stable storage at +2°C to +8°C. This randomized, double-blind, phase 2 study (NCT02193087) was performed in 1002 healthy dengue-naïve adults, 18–49 years of age, across seven centers in the USA to compare the safety and immunogenicity of one or two doses of a lyophilized TAK-003 formulation with the liquid TAK-003 formulation used in previous phase 1 studies. The primary objective was to show immunologic equivalence in terms of geometric mean titers (GMT) of neutralizing antibodies to the four dengue serotypes one month after one dose of the lyophilized and liquid formulations. Secondary assessments were of safety and seropositivity rates, including after a second dose. The primary endpoint was not met, because immunologic equivalence after one dose was only shown for the DENV-2 serotype. Nonetheless, GMTs and seropositivity rates to all four serotypes were achieved with all formulations after two doses and are in line with what was observed in previous studies. Additionally, in view of the acceptable reactogenicity, with no vaccine-related serious adverse events reported, these data support continuing further clinical development of the lyophilized TAK-003 formulation.